Bionomic Of Aedes Species And The Susceptibility To Insecticides In Penang Island, Malaysia - Mohd Ngesom, Ahmad Mohiddin (2015)
A field study was conducted in Flat Hamna (FH), Kampung Sungai Gelugor (KSG) and Kampung Tanjung Tokong (KTT) for a period of 14 months from January 2010 until February 2011. The objectives of this study are to determine the population and distribution of Aedes mosquito and the resistance status among the larvae and adult mosquitoes against selected insecticides that have been used in the vector control activity in Penang Island. The result showed that Ae. albopictus was a dominant species in Flat Hamna, Kampung Sungai Gelugor and Kampung Tanjung Tokong. It was found at higher frequency in both indoor and outdoor compared to Ae. aegypti. In indoor, overall Ae. albopictus accounts high number of larvae collection in Flat Hamna (28.59±1.10), Kampung Sungai Gelugor (19.94±1.59) and Kampung Tanjung Tokong (24.10±1.80) as compared to Ae. aegypti.